Normal bone mineral density and bone microarchitecture in adult males with high and low risk of exercise addiction - Hansen, Stinus Gadegaard; Lichtenstein, Mia Beck; Johansen, Karen Krogh; Støving, Rene Klinkby (Frontiers in Sports and Active Living, 2022)
Exercise addiction describes a pattern of excessive and obsessive exercise and is associated with hypoleptinemia and low testosterone that may have adverse skeletal effects. We conducted a cross-sectional study in males (aged 21 – 49 years) with high (n=20, exercise addictive) and low risk (n=20, exercise controls) of exercise addiction. We performed examinations of bone mass, bone microarchitecture and estimated bone strength using dual energy x-ray absorptiometry of the hip and spine and high-resolution peripheral quantitative computed tomography of the distal radius and tibia. Findings were compared to a population-based sample of healthy men aged 20-80 years (n=236). We found similar hip and spine bone mineral density in exercise addictive and controls. Cortical and trabecular bone microarchitecture and estimated bone strength in both radius and tibia did not differ significantly between the groups. Also, bone indices from both groups were within 95% prediction bands derived from the population-based sample for the vast majority of indices. There were no associations between circulation leptin or free testosterone and bone outcomes in either group. In conclusion, we found no associations between high risk of exercise addiction and various indices of bone mass and bone quality indicative of altered skeletal health.